Technology-intensive industries - Input-output analysis - Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2010)
By the analyses included in this paper I tried to quantify â using the input-output method â the amplitude of upstream and downstream linkages between manufacturing industries, structured by technological groups, for Romania and other six EU member countries, for comparison. Since intermediate products are the main carrier of knowledge diffused by high-tech industries towards other industries, by processing data from input-output tables we can obtain a measure of the inter-industry effects of these activities in an economy. In analyses we used statistical data on intermediate consumptions both from domestic production and imports, obtained from tables of intermediate product flows for 60 economic industries, of which 22 manufacturing ones (tables provided by Eurostat). For Romania, computations show a symmetrical distribution (on the technological ladder) of the intensity of upstream and downstream linkages of processing industries. This intensity is low in the area of low technologies, increases for medium technologies and then diminishes for high technologies. The main downstream intermediate flows of high technological level occur in the office equipment and computer industry and the chemical industry. As for the other ones, the relative level of the supplies of intermediate products provided by high and medium technology industries of Romania is lower in comparison with the other countries under consideration.
Keywords: D57; O33; 330; input-output analysis; technological progress; knowledge spillover